Pendampingan Rencana Pengeboran Sumber Mata Air Baru Bekerjasama dengan Badan Penanggulangan Bencana Daerah (BPBD) dan Badan Nasional Penanggulangan Bencana (BNPB) Lumajang sebagai Solusi Pemerataan Air Bersih - Zainil Ghulam; Nurhafid Ishari; Muhammad Abdul Halim Sidiq (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
This activity aims to learn about the focus of water problems in Gucialit Village. Through the initial survey, data was obtained that the uneven distribution of water sources was due to the lack of awareness of the residents so that the pipes that flowed to other residents' houses were channeled to their own homes, but this was not the only reason for the lack of clean water, another cause of this was the source of the springs, which began to shrink because part of the forest cover was cut down and converted into plantations. From the existing problems, the community together looks for suitable solutions to help the water problem in Sidomakmur Hamlet by looking for new springs devoted to the residents of Sidomakmur. In this case, the Sidomakmur community, in collaboration with the local government and BPBD (Regional Disaster Management Agency) and BNPB (National Disaster Management Agency), submitted a letter which finally BPBD went directly with the community to the location of the new spring and immediately examined the condition of the water.